Slightly Elevated Progesterone on HCG Trigger Day Has an Impact on Pregnancy Outcomes of Fresh Single Blastocyst Transfer Cycles Under an Early Follicular Phase Prolonged Protocol Cycle - Wei L; Zhao Y; Xu C; Zhang C (Dove Medical Press, 2022)
Longlong Wei,1,2 Yan Zhao,2 Chunyu Xu,1,2 Cuilian Zhang1,2 1Zhengzhou University People's Hospital, Zhengzhou, People's Republic of China; 2Department of Reproductive Medicine Center, Henan Provincial People's Hospital, Zhengzhou, People's Republic of ChinaCorrespondence: Cuilian Zhang, Department of Reproductive Medicine Center, Henan Provincial People's Hospital, Zhengzhou, People's Republic of China, Email zclian@zzu.edu.cnBackground: The effect of premature progesterone elevation on assisted reproductive technology has been debated. In different ovarian stimulation protocols, ovarian responses, and embryos transferred, conflicting results reside regarding the impact of elevated progesterone on pregnancy outcomes, according to previous studies. In addition, most studies have focused on significantly elevated progesterone levels, eg, above 1.5ng/mL, 1.75ng/mL, 2ng/mL. However, studies focusing on levels that are just slightly elevated are lacking, and some have concluded that such levels have no adverse effects on pregnancy outcomes.Methods: Clinical data of patients who underwent early follicular phase prolonged protocol cycle in vitro fertilization/intracytoplasmic sperm injection treatment were collected. Patients were divided into two groups according to progesterone level on the trigger day of human chorionic gonadotropin (HCG): Group 1: